Long‐Term Monitoring of Energetic Protons at the Bottom of Earth's Radiation Belt. Issue 1 (22nd January 2021) - Yoshioka, K.; Miyoshi, Y.; Kurita, S.; Teramoto, M.; Tsuchiya, F.; Yamazaki, A.; Murakami, G.; Kimura, T.; Kita, H.; Yoshikawa, I.; Kasaba, Y.
Abstract: The energetic particles in the Earth's radiation belt are known to fluctuate over various timescales. Although observations using satellites have been made for more than 50 years, there are few examples of continuous and long‐term observations at low altitude (<2, 000 km) and in low L ‐value ( L  < 2) regions, which are at the bottom of the inner radiation belt. This is because the orbits of satellites that are designed to cover large areas of the magnetosphere are not suitable for long‐term continuous observations at low altitudes. In this study, we focused on data from a space telescope that usually follows a low‐altitude circular orbit. The Hisaki space telescope, launched in 2013, continuously observes the planets from an altitude of ∼1, 000 km ( L ‐value 1–2). By using the noise component counted on the photodetector of Hisaki as a radiation monitor, the flux variation of the high‐energy protons (energy > 30 MeV) in this orbit can be observed. The results show a clear dependence on solar activity. At around L  = 2, it is found that the variation in the radiation belt proton flux is controlled by both the flux of the galactic cosmic rays and the neutral density of the thermosphere. The former one is the source process of high‐energy charged particles in the inner radiation belt, and the latter is the loss process due to the Coulomb collision. It is also found that the influence of galactic cosmic ray fluctuations becomes smaller as the L ‐value moves closer to 1. Key Points: The space telescope Hisaki made long‐term monitoring of high‐energy protons at ∼1, 000 km above the Earth's surface ( L  = 1–2) The high energy proton flux generated through the cosmic ray albedo neutron decay process shows evident L ‐value dependence and yearly variation There are significant amounts of high‐energy proton flux at ∼1, 000 km altitude which corresponds to the solar activity